Rainless Day Management using Geographic Information System and Wireless Sensor Networks on Climatology Station Banjarbaru - Raden Yani Gusriani; Munsyi M.T; Arum Murdianingsih (Universitas Nahdlatul Ulama Surabaya, 2022)
Information obtained at the Banjarbaru Climatology Station includes seasonal forecasts, rainfall analysis, rainfall properties analysis, rainy day analysis, and monitoring of rainless days in the South Kalimantan region. Monitoring of Rainless Day is a form of data on rainless days that occur in South Kalimantan in sequence. The data is sent by observers to the Banjarbaru Climatology Station office using SMS, WhatsApp, and even by calling the staff of the Banjarbaru Climatology Station so that employees must check every media both SMS, WhatsApp, and telephone to find out the data sent by observers. Related to these problems, a web-based rainless day monitoring application was made. By using the Research and Development (R&D) method to facilitate the management of rainless day data, a geographic information system management system using Google Maps API and MySQL database is built which is integrated with Internet of Things (IoT) technology based on Wireless Sensor Networks (WSN) for data collection in real-time. The system built will provide notifications in the management of areas affected by rainless days in order to deal with drought.